Historical Analysis of the Influence of Pre-Islamic Traditions in Jurisprudence and the Importance of Recontextualization - Asadurrohman, Muhammad (TAJDID, 2023)
This research attempts to provide readers with a contextual understanding of jurisprudence (fiqh) to encourage flexible and dynamic thinking. This study uses library research as its research methodology. The results indicated that Islam has theological significance to the content of older works, including the Torah, the Injīl, and Zabur. The backdrop context of the birth of Islam is influenced significantly by the Arab Jahiliyah period. It is of great importance to Jewish and Christian theology. Despite the presence of Arab Jahiliyah, the teachings of Islam align with the traditions and culture of Arab Jahiliyah. Jurisprudence is intricately linked to the historical and socio-political context in which it was developed. The recontextualization of jurisprudence in today's period is necessary to ensure the sustainability of Islamic teachings. This research's conclusions distinguish it from others by focusing on issues connected to fundamental and historical assumptions about Islamic teachings.